Crustal Imbrication in an Alpine Intraplate Mountain Range: A Wide‐Angle Cross‐Section Across the Spanish‐Portuguese Central System. Issue 7 (14th July 2022) - DeFelipe, I.; Ayarza, P.; Palomeras, I.; Ruiz, M.; Andrés, J.; Alcalde, J.; Poyatos, D. Martínez; Lodeiro, F. González; Yenes, M.; Elez, J.; Pérez‐Cáceres, I.; Torne, M.; et al.
Abstract: Intraplate ranges are topographic features that can occur far from plate boundaries, the expected position of orogens as described in the plate tectonics theory. To understand the lithospheric structure of intraplate ranges, we focused on the Spanish‐Portuguese Central System (SPCS), the most outstanding topographic feature in the central Iberian Peninsula. The SPCS is an Alpine range that exhumes Precambrian‐Paleozoic rocks and is located at >200 km from the northern border of the Iberian microplate. Here, we provide a P‐wave velocity model based on wide‐angle seismic reflection/refraction data of the central SPCS (Gredos sector). Our results show: (a) a layered lithosphere characterized by three major interfaces: Conrad, Mohorovicic, and Hales discontinuities, (b) an asymmetry of the crust‐mantle boundary under the SPCS, (c) the extent of the Variscan batholith forming the main outcrops of Gredos, and (d) the thinning of the lower crust toward the south. This model suggests that the exhumation of the SPCS basement was driven by a south‐vergent thick‐skinned thrust system, developed in the southern part of the SPCS and that promoted crustal imbrication and a Mohorovicic discontinuity's offset under the SPCS. Thus, the deformation mechanisms of the crust seem to be controlled by the presence of the late‐ to post‐Variscan granitoids that assimilated the Variscan mid‐crustal detachment creating a new rheological boundary. This tectonic structure allowed the formation of Alpine crustal‐scale thrust systems that eased coupled deformation of the upper and lower crust, leading to limited underthrusting of both crustal layers. Plain Language Summary: This study provides a lithospheric model of the Gredos sector of the Spanish‐Portuguese Central System (SPCS), a mountain range located in the central Iberian Peninsula. Despite most of the Alpine deformation in the Iberian Peninsula was accommodated along the Iberian microplate borders (i.e., Pyrenees, Cantabrian Mountains, and Betics), shortening was also transferred toward the interior, forming the SPCS. This mountain building process brought igneous and metasedimentary rocks of the Precambrian‐Paleozoic basement to the surface and contributed to the development of the Duero and Madrid Cenozoic basins, formed to the north and south of the SPCS. The SPCS exhibits a pop‐up/pop‐down structure with large‐scale fault systems in its southern boundary, showing an asymmetric crustal structure with an offset of the crust‐mantle discontinuity. The intrusion of granites during the Paleozoic had a large impact on the Alpine structure of the SPCS as they partially melted an older crust and erased previous discontinuities. Subsequently, the southern border of these granites represented weak zones that favored the nucleation of crustal‐scale faults during the Alpine contraction. Ultimately, this process exhumed the SPCS over the Madrid Cenozoic basin. Key Points: A wide‐angle seismic reflection/refraction profile (Spanish‐Portuguese Central System) revealed the Conrad, Moho, and Hales discontinuities The crustal structure under the Spanish‐Portuguese Central System shows a Moho offset of 6 km resulted from crustal‐scale thrust systems Variscan granitoids locally assimilated the mid‐crustal detachment (Conrad discontinuity) enhancing Alpine crustal‐coupled deformation